Eficiência de rizóbios para feijão caupi (Vigna unguiculata (L.) Walp) em áreas de agricultura familiar na Pré-amazônia maranhense - Silva Junior, Edilson Máximo da (2009)
Maranhão central north region is characterized as a place with acid, high contents of fine sand and low natural fertility soils, particularities wich are capable of hinder a more crop production. Therefore, nitrogen biological fixation has a strategic importance as the more appropriated economically and ecologically alternative for the empowerment of nitrogen in cowpea croping. This work aimed to study the behavior of specific 5 rhyzobia strains, wich are used in cowpea, in relation to nodulation and productivity of the cultivation, under three soil management systems in familiar agriculture in the state of Maranhão. Three surrounding areas were studied , under three different soil management systems, one under conventional cultivation (disc plowing and light disc harrowing), other a slash – and – burn system (on native vegetation) and a third one under alley-cropping system ( no-till system on leguminous trees straw with Clitória fairchildiana – alternative to slash-and-burn system). Experimental design was randomized block with four replicate and seven treatments. The treatments had two controls without inoculation, one without complement nitrogen and other fertilized with 74Kg of N ha-1, as urea form, besides more five treatments with Rhyzobia strains (BR3262, BR-3267, BR-3299, BR-3301 and BR-3302). Cowpea studied was BRS- Guariba. The experimental plots were divided in 6 lines of 6 meters of length, with 0,5 m between them and 10 seeds per meter. The number of fresh nodules, nodules dry weight, shoot dry mass and beans productivity (kg ha-1) were determined. The study showed that about beans nodulation parameters, growth and production there was differences between agricultural management system standing out slash- and- burn system and worst conditions under conventional cultivation system. For the productivity parameter only under conventional system was not verified inoculation treatments effects. On alley cropping system only BR- 3302 and BR- 3267 strains were capable to develop cowpea productivity up to 42%, regarding to control without N. For the slash-and-burn system all strains were capable of increase productivity in relation to control without N, nevertheless higher productivity was verified on control with mineral-N , more than 1600 kg ha-1 . Under this system stood out BR-3302 and BR-3299 strains with productivity close to 1200 kg ha-1, against 600 kg from control without N. It represents a productivity increase about 180% in relation to the State average, that is a something around 400 kg ha-1 . Therefore it was verified that magnitude and cowpea response pattern to inoculation was associated to rhyzobia strains that had been studied and to the managemet system used by familiar farmers from this region.